THE IMPACT OF THE COVID-19 PANDEMIC ON NON-PERFORMING LOANS IN THE BANKING SECTOR - Diana Elena BRINZA; Mihaela Iuliana DUMITRU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
When there are indications that the borrower is likely not to repay the loan or if more than 90 days have passed without the borrower having paid the agreed instalments, these loans are considered non-performing loans. This can happen when a person loses his job and therefore cannot repay a mortgage under the agreed conditions, or when a company is facing financial problems, which is common in the current situation. Thus, in the current conditions, an increase in the level of non-performing loans is inherent, in the absence of protection measures. In this article, there were analyzed the measures taken by the Central Banks of the European Union to mitigate the effects of the COVID-19 pandemic, the actions taken by the National Bank of Romania in this context, as well as the necessary measures to be taken further by credit institutions in order to preserve their capital and liquidity and implicitly for the management of the stock of non-performing loans.